Detection and identification of gastrointestinal microsporidia using non-invasive techniques. - Corcoran, G D (1995)
AIMS--To detect enteric microsporidia in faecal specimens from patients with the acquired immunodeficiency syndrome (AIDS), and to identify the spores to species level without using invasive procedures. METHODS--Formalised faecal preparations were examined using a modification of the strong trichrome staining method to demonstrate microsporidian spores. Six positive specimens were prepared for electron microscopy by emulsification and separation using a 9% Ficoll gradient. RESULTS--The modified staining technique readily identified microsporidian spores. Spores of different species showed variation in size. Identification using electron microscopy was successful for five of the six positive specimens examined. It was unsuccessful for one specimen in which spores were less abundant on initial staining. CONCLUSIONS--The modified strong trichrome staining method is a useful way of detecting spores of intestinal microsporidia in faecal specimens. Variation in spore size may permit provisional identification by light microscopy. Electron microscopic examination of faecal preparations is useful for identifying spores to species level.